الصكوك الإسلامية ودورها في تعبئة المدخرات العائلية في الجزائر: Islamic Sukuk and their Role in Mobilizing Family Savings in Algeria - موسوس مغنية; صافر وسام (Journal of North African Economies, 2025)
This study aims to identify the role of Islamic sukuks in mobilizing Algerian families’ savings, by clarifying the concepts related to Islamic sukuks and family savings with reference to the case of Algeria, and reviewing the development of family savings ratios in it in relation to the gross domestic product, then focusing more on Islamic banking savings vessels. And the requirements that the Algerian government must provide to develop work with this tool. We have concluded from this study that the existing Islamic banking systems in Algeria, which are claimed to be developed, have yielded some fruits, but they have not been able to attract a large proportion of family savings circulating outside the banking system due to the recent use of them, and as a result of the obstacles they face. Therefore, developing the work with Islamic Sukuk will be a positive change station. It is an effective mechanism for absorbing family savings, as it takes into account the controls of Islamic Sharia, the privacy of those with low incomes, and is negotiable among individuals. This idea was proposed in Monetary and Banking Law No. 23-09 of 2023, and to ensure the success of its work, several requirements must be provided, including a financial market that encourages trading these Sukuk.